Variation Tolerant On-Chip Interconnects - Nigussie, Ethiopia Enideg (Analog Circuits and Signal Processing, 2012)
This book presents design techniques, analysis and implementation of high performance and power efficient, variation tolerant on-chip interconnects.  Given the design paradigm shift to multi-core, interconnect-centric designs and the increase in sources of variability and their impact in sub-100nm technologies, this book will be an invaluable reference for anyone concerned with the design of next generation, high-performance electronics systems. Provides comprehensive, circuit-level explanation of high-performance, energy-efficient, variation-tolerant on-chip interconnect; Describes design techniques to mitigate problems caused by variation; Includes techniques for design and implementation of self-timed on-chip interconnect, delay variation insensitive communication protocols, high speed signaling techniques and circuits, bit-width independent completion detection and process, voltage and temperature variation tolerance.                          .